Photocurable composition, sealing material for liquid crystal display device, and liquid crystal display device

By using a photocurable composition of a multifunctional curable resin and an inorganic filler material, the problem of poor curing and degradation of adhesiveness when the substrate is low in heat resistance is solved, and high-efficiency photocuring and excellent Spraying sex.

CN119213047APending Publication Date: 2024-12-27MITSUI CHEMICALS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380023377.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-11
Filing Date
2023-03-06
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The conventional liquid crystal display element sealant has poor curing when the substrate has low heat resistance, and its adhesiveness decreases only when photocuring is light, which affects productivity and nozzle ejectionability.

Method used

Using a photocurable composition containing a multifunctional curable resin having more than two ethylene unsaturated double bonds, a photopolymerization initiator and an inorganic filler material, the adhesion and spraying are improved through specific compound ratios and structural design. sex.

Benefits of technology

High-efficiency light curing on a low heat resistance substrate is achieved, the adhesion and productivity of the liquid crystal display device are improved, and the excellent ejection performance of the nozzle is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213047A_ABST
    Figure CN119213047A_ABST
Patent Text Reader

Abstract

The photocurable composition includes a curable resin component, a photopolymerization initiator, and an inorganic filler. The curable resin component contains a polyfunctional curable compound having two or more ethylenically unsaturated double bonds. The polyfunctional curable compound includes a first polyfunctional curable compound and a second polyfunctional curable compound that are different from each other. The content ratio of the polyfunctional curable compound is from 85 parts by mass to 100 parts by mass (inclusive) with respect to 100 parts by mass of the curable resin component. And a viscosity at 25 DEG C of from 200000 mPa * s to 400000 mPa * s (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photocurable composition, a sealing material for a liquid crystal display device, and a liquid crystal display device. Background Art

[0002] In the past, liquid crystal display elements (such as liquid crystal display units) were manufactured by liquid crystal dripping. In this method, a sealant containing a curable resin, a photo-radical polymerization initiator and / or a thermal radical polymerization initiator is first applied to the periphery of the surface of a substrate with an electrode to form a roughly rectangular seal pattern. Then, in the uncured state of the sealant, droplets of liquid crystal are added into the seal pattern frame provided on the substrate. Then, in a vacuum, another electrode substrate is bonded to the surface of one electrode substrate, and the sealant is cured (photocured and / or thermally cured) to manufacture a liquid crystal display element.

[0003] As a sealant used in the liquid crystal dropping method, a sealant for a liquid crystal display element containing, for example, bisphenol A epoxy acrylate, a thermal radical polymerization initiator, and a photoradical polymerization initiator has been proposed (for example, see Example 8 of Patent Document 1). Such a sealant for a liquid crystal display element is cured by heating after light irradiation.

[0004] In addition, Patent Document 1 above proposes a liquid crystal display element sealant containing bisphenol A epoxy acrylate and a photoradical polymerization initiator without a thermal radical polymerization initiator (for example, see Example 9 of Patent Document 1). Such a liquid crystal display element sealant is cured only by light irradiation without heating.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2016 / 194871 Pamphlet Summary of the invention

[0008] Problem that the invention aims to solve

[0009] On the other hand, in Example 8 of Patent Document 1, since the sealant for the liquid crystal display element is cured by heating, there is a disadvantage that the sealant cannot be cured when the heat resistance of the substrate is low. In addition, there is a disadvantage that the productivity is reduced by implementing the heating process.

[0010] However, if the sealant is cured only by photocuring as in Example 9 of Patent Document 1, there is a problem in that the adhesiveness is reduced.

[0011] Furthermore, when the sealing agent is ejected from a nozzle, ejection properties from the nozzle are required.

[0012] The present invention provides a photocurable composition having excellent adhesiveness and dischargeability from a nozzle, a sheet for a liquid crystal display device comprising the photocurable composition, and a liquid crystal display device having a cured product of the sheet for a liquid crystal display device.

[0013] Methods used to solve problems

[0014] The present invention [1] is a photocurable composition comprising a curable resin component, a photopolymerization initiator and an inorganic filler; the curable resin component comprises a polyfunctional curable compound having two or more ethylenically unsaturated double bonds; the polyfunctional curable compound comprises a first polyfunctional curable compound and a second polyfunctional curable compound that are different from each other; the content of the polyfunctional curable compound is 85 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of the curable resin component, and the viscosity at 25°C is 200,000 mPa·s or more and 400,000 mPa·s or less.

[0015] The present invention [2] comprises the photocurable composition described in the above [1], wherein either the first multifunctional curable compound or the second multifunctional curable compound is epoxy (meth) acrylate; the epoxy (meth) acrylate is a reaction product of an epoxy compound and a carboxyl group-containing vinyl monomer; the carboxyl group-containing vinyl monomer is a reaction product of a hydroxyl group-containing vinyl monomer and a polyacid, and the epoxy (meth) acrylate is a compound represented by the following formula (1).

[0016] [Chemistry 1] Chemical 1

[0017]

[0018] (In the above formula (1), R1 represents a hydrogen atom or a methyl group, R2 represents a structure derived from a hydroxyl group-containing vinyl monomer, and R3 represents a structure derived from a polybasic acid.)

[0019] The present invention [3] comprises the photocurable composition according to the above [1] or [2], wherein the content of the inorganic filler is 10% by mass or more.

[0020] The present invention [4] comprises the photocurable composition according to any one of [1] to [3], wherein the inorganic filler is at least one selected from the group consisting of silica, alumina and talc.

[0021] The present invention [5] comprises the photocurable composition according to any one of [1] to [4], further comprising a coupling agent.

[0022] The present invention [6] comprises the photocurable composition according to any one of [1] to [5], further comprising composite particles, wherein the composite particles include a core and a shell covering the core.

[0023] The present invention [7] comprises the photocurable composition according to any one of [1] to [6], wherein the photopolymerization initiator has at least one skeleton selected from the group consisting of an oxime ester skeleton, a thioxanthone skeleton and an anthraquinone skeleton.

[0024] The present invention [8] includes a sealing material for a liquid crystal display device, comprising the photocurable composition described in any one of [1] to [7].

[0025] The present invention [9] includes a liquid crystal display device, which comprises: a first electrode-bearing substrate; a second electrode-bearing substrate, which is arranged relative to the above-mentioned first electrode-bearing substrate; a liquid crystal, which is interposed between the above-mentioned first electrode-bearing substrate and the above-mentioned second electrode-bearing substrate; and a cured product of the sealing material for the liquid crystal display device described in the above-mentioned [8], which bonds the peripheral end portions of the above-mentioned first electrode-bearing substrate and the above-mentioned second electrode-bearing substrate.

[0026] The present invention

[10] includes the liquid crystal display device described in the above [9], wherein the substrate in the first substrate with an electrode and the second substrate with an electrode is a polymer film.

[0027] Effects of the Invention

[0028] The curable resin component of the photocurable composition of the present invention includes a polyfunctional curable compound having two or more ethylenically unsaturated double bonds. In addition, the polyfunctional curable compound includes a first polyfunctional curable compound and a second polyfunctional curable compound that are different from each other. In addition, the content ratio of the polyfunctional curable compound is within a predetermined range. In addition, the photocurable composition includes an inorganic filler. In addition, the viscosity of the photocurable composition at 25° C. is within a predetermined range. Therefore, the adhesiveness and the ejection property from the nozzle are excellent.

[0029] The sealing material for a liquid crystal display device of the present invention contains the photocurable composition of the present invention, and therefore has excellent adhesiveness and discharge properties from a nozzle.

[0030] The liquid crystal display device of the present invention includes the cured product of the sealing material for a liquid crystal display device of the present invention, and therefore has excellent adhesiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] [Figure 1] Figure 1A to Figure 1C A method for manufacturing a liquid crystal display device by a liquid crystal dropping method using a sealing material for a liquid crystal display device is shown. Figure 1AThe figure shows a step of applying a sealing material for a liquid crystal display device to the outer periphery of the surface of one substrate with an electrode to form a substantially rectangular sealing pattern. Figure 1B The process of dropping droplets of liquid crystal into the seal pattern frame of one electrode-equipped substrate 1 is shown in a state where the sealing material for a liquid crystal display device is not cured. Figure 1C The process of manufacturing a liquid crystal display device is described in which one substrate with electrodes is bonded to the surface of another substrate with electrodes under vacuum, and a sealing material for a liquid crystal display device is photocured. DETAILED DESCRIPTION

[0032] The photocurable composition contains a curable resin component, a photopolymerization initiator, and an inorganic filler.

[0033] <Curing Resin Component>

[0034] The curable resin component contains a polyfunctional curable compound.

[0035] The polyfunctional curable compound has two or more ethylenically unsaturated double bonds.

[0036] As the multifunctional curable compound, for example, multifunctional epoxy (meth) acrylate, multifunctional (meth) alkyl acrylate and multifunctional urethane (meth) acrylate can be cited. As the multifunctional curable compound, preferably multifunctional epoxy (meth) acrylate can be cited. It should be noted that (meth) acrylate refers to methacrylate and / or acrylate.

[0037] As the polyfunctional epoxy (meth)acrylate, for example, a first polyfunctional epoxy (meth)acrylate which is a reaction product of an epoxy compound and a carboxyl group-containing vinyl monomer can be mentioned.

[0038] Examples of epoxy compounds include bifunctional epoxy compounds. Examples of bifunctional epoxy compounds include diglycidyl ether compounds. Examples of diglycidyl ether compounds include bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, bisphenol S diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerol diglycidyl ether, and neopentyl glycol diglycidyl ether. Examples of epoxy compounds include bisphenol A diglycidyl ether.

[0039] The epoxy compounds can be used alone or in combination of two or more.

[0040] Examples of the carboxyl group-containing vinyl monomer include (meth)acrylic acid, maleic anhydride, maleic acid, fumaric acid, itaconic acid, and crotonic acid.

[0041] In addition, as the carboxyl group-containing vinyl monomer, a reaction product of a hydroxyl group-containing vinyl monomer and a polybasic acid can also be mentioned.

[0042] As the hydroxyl-containing vinyl monomer, for example, a hydroxyl-containing acrylic monomer can be cited. As the hydroxyl-containing acrylic monomer, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate can be cited. As the hydroxyl-containing vinyl monomer, preferably 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate can be cited. As the hydroxyl-containing vinyl monomer, more preferably 2-hydroxyethyl acrylate and 2-hydroxypropyl acrylate can be cited.

[0043] The hydroxyl group-containing vinyl monomers may be used alone or in combination of two or more.

[0044] Examples of the polybasic acid include saturated dibasic acids, and examples of the saturated dibasic acid include saturated aliphatic dibasic acids, saturated alicyclic dibasic acids, and aromatic dibasic acids.

[0045] Examples of the saturated aliphatic dibasic acid include oxalic acid, malonic acid, succinic acid, methylsuccinic acid, 2,2-dimethylsuccinic acid, 2,3-dimethylsuccinic acid, hexylsuccinic acid, glutaric acid, 2-methylglutaric acid, 3-methylglutaric acid, 2,2-dimethylglutaric acid, 3,3-dimethylsuccinic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and anhydrides thereof. Preferred examples of the saturated aliphatic dibasic acid include succinic anhydride.

[0046] Examples of the saturated alicyclic dibasic acid include chlorobridgeic acid, 1,2-hexahydrophthalic acid, 1,1-cyclobutanedicarboxylic acid, and anhydrides thereof.

[0047] Examples of the aromatic dibasic acid include phthalic acid (phthalic acid, isophthalic acid, terephthalic acid), trimellitic acid, pyromellitic acid, and anhydrides thereof.

[0048] As the aromatic dibasic acid, preferably, phthalic acid is used.

[0049] Preferred examples of the polybasic acid include saturated aliphatic dibasic acids and aromatic dibasic acids.

[0050] The polybasic acid may be used alone or in combination of two or more.

[0051] Then, in order to react the hydroxyl-containing vinyl monomer with the polybasic acid, the hydroxyl-containing vinyl monomer, the polybasic acid, and, if necessary, a polymerization inhibitor (for example, p-methoxyphenol) are mixed and heated.

[0052] In the above reaction, the carboxyl groups of the polybasic acid are blended in the hydroxyl-containing vinyl monomer in an amount of, for example, 1.8 mol or more and 2.2 mol or less per 1 mol of the hydroxyl groups in the hydroxyl-containing vinyl monomer.

[0053] In the above reaction, the reaction temperature is, for example, 60° C. or higher, preferably 80° C. or higher, and, for example, 120° C. or lower, preferably 100° C. or lower. The reaction time is, for example, 1 hour or higher, and, for example, 12 hours or lower.

[0054] Thereby, a carboxyl group-containing vinyl monomer can be obtained as a reaction product of a hydroxyl group-containing vinyl monomer and a polybasic acid.

[0055] As the carboxyl-containing vinyl monomer, preferably, the reaction product of a hydroxyl-containing vinyl monomer and a polyacid can be cited. As the carboxyl-containing vinyl monomer, more preferably, the reaction product of 2-hydroxyethyl acrylate and succinic anhydride, the reaction product of 2-hydroxypropyl acrylate and phthalic anhydride, the reaction product of 2-hydroxypropyl acrylate and succinic anhydride, the reaction product of 2-hydroxyethyl acrylate and phthalic anhydride, and the reaction product of 2-hydroxyethyl methacrylate and succinic anhydride can be cited. As the carboxyl-containing vinyl monomer, further preferably, the reaction product of 2-hydroxypropyl acrylate and succinic anhydride and the reaction product of 2-hydroxyethyl acrylate and phthalic anhydride can be cited.

[0056] The carboxyl group-containing vinyl monomers may be used alone or in combination of two or more.

[0057] Then, in order to react the epoxy compound with the carboxyl group-containing vinyl monomer, the epoxy compound and the carboxyl group-containing vinyl monomer are mixed and heated.

[0058] In the above reaction, the epoxy compound is blended so that the carboxyl groups of the carboxyl group-containing vinyl monomer are, for example, 1.8 mol or more and 2.2 mol or less per 1 mol of the epoxy groups of the epoxy compound.

[0059] In the above reaction, the reaction temperature is, for example, 60° C. or higher, preferably 80° C. or higher, and for example, 120° C. or lower, preferably 100° C. or lower. The reaction time is, for example, 1 hour or higher, and for example, 12 hours or lower.

[0060] Thus, the first multifunctional epoxy (meth)acrylate can be obtained.

[0061] Among such first multifunctional epoxy (meth)acrylates, preferably, there can be mentioned compounds represented by the following formula (1).

[0062] [Chemistry 2]Chemistry 2

[0063]

[0064] In the above formula (1), R1 represents a hydrogen atom or a methyl group.

[0065] In addition, in the above formula (1), R2 represents a structure derived from the above hydroxyl-containing vinyl monomer. In detail, when the hydroxyl-containing vinyl monomer is represented by the following formula (2), R2 represents X. In detail, X represents an alkylene group corresponding to the alkyl group of the hydroxyalkyl ester in the hydroxyl-containing vinyl monomer. In more detail, X represents an alkylene group having a carbon number of 1 or more and 4 or less. In further detail, it represents an ethylene group and a 2-propylene group.

[0066] [Chemistry 3]Chemistry 3

[0067]

[0068] In the above formula (1), R3 represents a structure derived from the above polyacid. Specifically, when the polyacid is represented by HOOC-Y-COOH, R3 represents Y. Specifically, Y is a divalent bonding group. As the bonding group, for example, bonding groups that do not contain aromatic rings and alicyclic rings, bonding groups that contain aromatic rings, and bonding groups that contain alicyclic rings can be listed. As bonding groups that do not contain aromatic rings and alicyclic rings, for example, alkylene groups having a carbon number of 1 to 20 can be listed. As alkylene groups having a carbon number of 1 to 20, for example, linear alkylene groups having a carbon number of 1 to 20 and branched alkylene groups having a carbon number of 1 to 20 can be listed. As linear alkylene groups having a carbon number of 1 to 20, for example, methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, decylene, dodecylene, tetradecylene, hexadecylene, octadecylene, and eicosylene can be listed. Examples of branched alkylene groups having 1 to 20 carbon atoms include isopropylene, isobutylene, sec-butylene, tert-butylene, isopentylene, sec-pentylene, 2-methylhexylene, 2-ethylhexylene, and isodecylene. Examples of aromatic ring-containing bonding groups include phenylene, naphthylene, and anthrylene. Examples of alicyclic ring-containing bonding groups include cyclohexylene and cyclopentylene.

[0069] In addition, among such first multifunctional epoxy (meth)acrylates, preferred examples include a compound represented by the following formula (3) (hereinafter referred to as compound (3), a compound represented by the following formula (4) (hereinafter referred to as compound (4), a compound represented by the following formula (5) (hereinafter referred to as compound (5), a compound represented by the following formula (6) (hereinafter referred to as compound (6), and a compound represented by the following formula (7) (hereinafter referred to as compound (7).

[0070] [Chemistry 4]

[0071] Chemical 4

[0072] As the first multifunctional epoxy (meth)acrylate, more preferably, the compound (5) and the compound (6) are mentioned.

[0073] A commercially available product may be used as the first multifunctional epoxy (meth)acrylate. Examples of such commercially available products include Ebecryl 3701 (compound (5), manufactured by Daicel-Allnex Corporation).

[0074] In addition, as a multifunctional epoxy (meth) acrylate, for example, a second multifunctional epoxy (meth) acrylate can be listed, which is obtained by ring-opening the above-mentioned epoxy compound (preferably bisphenol A diglycidyl ether) using the above-mentioned polyacid (preferably phthalic anhydride), modifying it with ε-caprolactone, and then reacting it with the above-mentioned hydroxyl-containing vinyl monomer.

[0075] Specific examples of such second multifunctional epoxy (meth)acrylates include compounds represented by the following formula (8) (hereinafter referred to as compound (8)).

[0076] [Chemistry 5]Chemistry 5

[0077]

[0078] In the above formula (8), n represents an integer of 1 to 3.

[0079] A commercially available product may also be used as the second multifunctional epoxy (meth)acrylate. Examples of such commercially available products include Ebecryl 3708 (compound (8), manufactured by Daicel-Allnex Corporation).

[0080] The polyfunctional curable compound is not used alone, but two or more types are used in combination. That is, the polyfunctional curable compound includes a first polyfunctional curable compound and a second polyfunctional curable compound that are different from each other.

[0081] It is preferred to use two types of polyfunctional curable compounds in combination. That is, the polyfunctional curable compound includes a first polyfunctional curable compound and a second polyfunctional curable compound.

[0082] Furthermore, it is more preferred that: both the first multifunctional curable compound and the second multifunctional curable compound are the first multifunctional epoxy (meth) acrylate, or both the first multifunctional curable compound and the second multifunctional curable compound are the second multifunctional epoxy (meth) acrylate, or one of the first multifunctional curable compound and the second multifunctional curable compound is the first multifunctional epoxy (meth) acrylate and the other is the second multifunctional epoxy (meth) acrylate.

[0083] More preferably, one of the first polyfunctional curable compound and the second polyfunctional curable compound is a first polyfunctional epoxy (meth)acrylate, and the other is a second polyfunctional epoxy (meth)acrylate.

[0084] In such a case, the content ratio of the first polyfunctional epoxy (meth)acrylate relative to the curable resin component is, for example, 30 mass % or more, preferably 45 mass % or more, and, for example, 80 mass % or less, preferably 60 mass % or less.

[0085] The content ratio of the first multifunctional epoxy (meth)acrylate relative to 100 parts by mass of the total amount of the first multifunctional epoxy (meth)acrylate and the second multifunctional epoxy (meth)acrylate is, for example, 30 parts by mass or more, preferably 45 parts by mass or more, and, for example, 90 parts by mass or less, preferably 60 parts by mass or less.

[0086] The content ratio of the second multifunctional epoxy (meth)acrylate relative to the curable resin component is, for example, 5 mass % or more, preferably 20 mass % or more, more preferably 35 mass % or more, and, for example, 65 mass % or less, preferably 55 mass % or less.

[0087] In addition, the content ratio of the second multifunctional epoxy (meth)acrylate relative to 100 parts by mass of the total amount of the first multifunctional epoxy (meth)acrylate and the second multifunctional epoxy (meth)acrylate is, for example, 10 parts by mass or more, preferably 40 parts by mass or more, and, for example, 70 parts by mass or less, preferably 55 parts by mass or less.

[0088] The mass ratio of the content of the first multifunctional epoxy (meth) acrylate to the content of the second multifunctional epoxy (meth) acrylate is, for example, 0.90 or more, preferably 0.95 or more, more preferably 1.01 or more, further preferably 1.10 or more, and is, for example, 8.00 or less, preferably 3.00 or less, more preferably 1.50 or less, further preferably 1.30 or less, and particularly preferably 1.20 or less.

[0089] In addition, it is more preferred that the viscosity of the first polyfunctional curable compound is higher than the viscosity of the second polyfunctional curable compound. In other words, it is more preferred that the polyfunctional curable compound includes a first polyfunctional curable compound having a relatively high viscosity and a second polyfunctional curable compound having a relatively low viscosity.

[0090] When the polyfunctional curable compound includes a first polyfunctional curable compound having a relatively high viscosity and a second polyfunctional curable compound having a relatively low viscosity, both adhesiveness and dischargeability from a nozzle can be achieved.

[0091] In such a case, the viscosity of the first multifunctional curable compound at 60° C. is, for example, 5000 mPa·s or more, and for example, 9000 mPa·s or less.

[0092] The viscosity of the second multifunctional curable compound at 60° C. is, for example, 2000 mPa·s or more, and for example, less than 5000 mPa·s.

[0093] The ratio of the viscosity of the first polyfunctional curable compound at 60° C. to the viscosity of the second polyfunctional curable compound at 60° C. is more than 1, preferably 1.5 or more, and for example, 5 or less.

[0094] In addition, the measuring method of the said viscosity is demonstrated in detail in the Example mentioned later.

[0095] In such a case, the content ratio of the first polyfunctional curable compound relative to the curable resin component is, for example, 30 mass % or more, preferably 45 mass % or more, and, for example, 80 mass % or less, preferably 60 mass % or less.

[0096] The content ratio of the first polyfunctional curable compound relative to 100 parts by mass of the total amount of the first polyfunctional curable compound and the second polyfunctional curable compound is, for example, 30 parts by mass or more, preferably 45 parts by mass or more, and for example, 90 parts by mass or less, preferably 60 parts by mass or less.

[0097] The content ratio of the second multifunctional curable compound relative to the curable resin component is, for example, 5 mass % or more, preferably 20 mass % or more, more preferably 35 mass % or more, and, for example, 65 mass % or less, preferably 55 mass % or less.

[0098] The content ratio of the second polyfunctional curable compound relative to 100 parts by mass of the total amount of the first polyfunctional curable compound and the second polyfunctional curable compound is, for example, 10 parts by mass or more, preferably 40 parts by mass or more, and for example, 70 parts by mass or less, preferably 55 parts by mass or less.

[0099] The mass ratio of the content of the first polyfunctional curable compound to the content of the second polyfunctional curable compound is, for example, 0.90 or more, preferably 0.95 or more, more preferably 1.01 or more, further preferably 1.10 or more, and is, for example, 8.00 or less, preferably 3.00 or less, more preferably 1.50 or less, further preferably 1.30 or less, and particularly preferably 1.20 or less.

[0100] Furthermore, it is more preferred that the first polyfunctional curable compound having a relatively high viscosity is a first polyfunctional epoxy (meth)acrylate, and the second polyfunctional curable compound having a relatively low viscosity is a second polyfunctional epoxy (meth)acrylate.

[0101] The content of the polyfunctional curable compound is 85 parts by mass or more, preferably 90 parts by mass or more, more preferably 95 parts by mass or more, and is 100 parts by mass or less, based on 100 parts by mass of the curable resin component.

[0102] When the content of the polyfunctional curable compound is not less than the above lower limit, the adhesiveness and the discharge property from the nozzle can be improved.

[0103] On the other hand, when the content ratio of the multifunctional curable compound is less than the above lower limit, the adhesiveness and the discharge property from the nozzle are reduced.

[0104] In addition, the curable resin component contains a monofunctional curable compound as necessary.

[0105] Examples of the monofunctional curable compound include monofunctional epoxy (meth)acrylates, monofunctional alkyl (meth)acrylates, and monofunctional urethane (meth)acrylates. Preferably, the monofunctional curable compound includes monofunctional alkyl (meth)acrylates.

[0106] Examples of the monofunctional alkyl (meth)acrylate include monofunctional alkyl (meth)acrylates not containing a ring structure and monofunctional alkyl (meth)acrylates containing a ring structure.

[0107] Examples of the monofunctional alkyl (meth)acrylate not containing a ring structure include alkyl (meth)acrylates having a carbon number of 1 to 20. Examples of the alkyl (meth)acrylate having a carbon number of 1 to 20 include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, and lauryl (meth)acrylate.

[0108] Examples of the monofunctional alkyl (meth)acrylate containing a ring structure include isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and dicyclopentanyl (meth)acrylate.

[0109] As the monofunctional alkyl (meth)acrylate, preferably a monofunctional alkyl (meth)acrylate containing a ring structure can be cited. As the monofunctional alkyl (meth)acrylate, more preferably dicyclopentenyloxyethyl (meth)acrylate can be cited. As the monofunctional alkyl (meth)acrylate, more preferably dicyclopentenyloxyethyl acrylate can be cited. As the monofunctional alkyl (meth)acrylate, more preferably dicyclopentenyloxyethyl acrylate can be cited.

[0110] The monofunctional curable compound can be used alone or in combination of two or more.

[0111] The content ratio of the monofunctional curable compound relative to 100 parts by mass of the curable resin component is, for example, 0 parts by mass or more, and for example, 15 parts by mass or less, preferably 10 parts by mass or less, and more preferably 5 parts by mass or less.

[0112] When the content ratio of the monofunctional curable compound is equal to or less than the above upper limit, adhesiveness and dischargeability from a nozzle can be improved.

[0113] It is preferred that the curable resin component does not contain a monofunctional curable compound but contains a polyfunctional curable compound.

[0114] The content ratio of the curable resin component with respect to the photocurable composition is 80 mass % or more, preferably 85 mass % or more, and for example, 95 mass % or less.

[0115] <Photopolymerization Initiator>

[0116] As the photopolymerization initiator, a known photopolymerization initiator can be selected.

[0117] The photopolymerization initiator preferably has at least one skeleton selected from the group consisting of an oxime ester skeleton, a thioxanthone skeleton, and an anthraquinone skeleton.

[0118] When the photopolymerization initiator preferably has at least one skeleton selected from the group consisting of an oxime ester skeleton, a thioxanthone skeleton, and an anthraquinone skeleton, photocuring is excellent.

[0119] Examples of the photopolymerization initiator having an oxime ester skeleton include 1-(4-(phenylthio)phenyl)-1,2-octanedione 2-(O-benzoyloxime), ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetyloxime). Examples of the photopolymerization initiator having an oxime ester skeleton include ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetyloxime).

[0120] Examples of the photopolymerization initiator having a thioxanthone skeleton include 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, and 1-chloro-4-propoxythioxanthone as thioxanthone compounds.

[0121] In addition, as the photopolymerization initiator having a thioxanthone skeleton, a compound having a thioxanthone skeleton described in International Publication No. 2017 / 002362 may be used.

[0122] Examples of the photopolymerization initiator having an anthraquinone skeleton include 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-chloroanthraquinone, and 2-amylanthraquinone.

[0123] In addition, as the photopolymerization initiator having an anthraquinone skeleton, a compound having a thioxanthone skeleton described in International Publication No. 2017 / 002362 may also be used.

[0124] The photopolymerization initiator more preferably has an oxime ester skeleton. That is, the photopolymerization initiator more preferably includes a photopolymerization initiator having an oxime ester skeleton.

[0125] The photopolymerization initiator can be used alone or in combination of two or more.

[0126] The content ratio of the photopolymerization initiator relative to 100 parts by mass of the curable resin component is, for example, 0.1 parts by mass or more, preferably 0.3 parts by mass or more, and, for example, 3 parts by mass or less, preferably 1 part by mass or less.

[0127] The content ratio of the photopolymerization initiator relative to the photocurable composition is, for example, 0.1 mass % or more, preferably 0.3 mass % or more, and, for example, 5 mass % or less, preferably 1 mass % or less.

[0128] <Inorganic filler>

[0129] The inorganic filler is added to improve the adhesiveness. In addition, the viscosity can be adjusted by adding the inorganic filler, thereby improving the ejection property from the nozzle.

[0130] Examples of the inorganic filler include oxides (eg, alumina), hydroxides, carbonates, sulfates, silicon dioxide, talc, silicates, fluorides, phosphates, and clay minerals.

[0131] The inorganic filler is preferably at least one selected from the group consisting of silica, alumina, and talc.

[0132] If the inorganic filler is at least one selected from the group consisting of silica, alumina, and talc, the adhesiveness and the ejection property from the nozzle can be further improved.

[0133] The inorganic filler may be used alone or in combination of two or more.

[0134] The content of the inorganic filler relative to 100 parts by mass of the curable resin component is, for example, 5 parts by mass or more, preferably 10 parts by mass or more, and from the viewpoint of improving adhesion, more preferably 15 parts by mass or more, and, for example, 30 parts by mass or less.

[0135] The content ratio of the inorganic filler relative to the photocurable composition is, for example, 5% by mass or more, preferably 10% by mass or more from the viewpoint of improving adhesion, more preferably 15% by mass or more from the viewpoint of further improving adhesion, and, for example, 30% by mass or less.

[0136] <Method for producing photocurable composition>

[0137] The photocurable composition is obtained by mixing a curable resin component, a photopolymerization initiator, and an inorganic filler.

[0138] In addition, composite particles may be preferably blended in the above mixing. That is, the photocurable composition preferably contains composite particles.

[0139] The composite particles are blended to improve adhesion.

[0140] The composite particles include a core and a shell covering the core.

[0141] Specifically, the core and the shell are, for example, polymers of alkyl (meth)acrylates. Examples of alkyl (meth)acrylates include alkyl (meth)acrylates having an alkyl moiety with a carbon number of 1 to 12. Examples of alkyl (meth)acrylates having an alkyl moiety with a carbon number of 1 to 12 include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate.

[0142] Preferred examples of such composite particles include composite particles in which the core is a polymer of n-butyl acrylate and the shell is a polymer of methyl methacrylate.

[0143] In addition, in such composite particles, the glass transition temperature of the shell is higher than the glass transition temperature of the core.

[0144] Commercially available composite particles may be used. Examples of commercially available composite particles include ZEFIAC F351 (manufactured by AICA Industries, Ltd.).

[0145] The content ratio of the composite particles relative to 100 parts by mass of the curable resin component is, for example, 1 part by mass or more, preferably 5 parts by mass or more, more preferably 8 parts by mass or more, and for example, 20 parts by mass or less, preferably 10 parts by mass or less.

[0146] In addition, a coupling agent may be blended in the above mixing. That is, the photocurable composition contains a coupling agent.

[0147] The coupling agent is added to improve adhesion.

[0148] The coupling agent is not particularly limited. Examples of the coupling agent include epoxy-containing silane coupling agents, amino-containing silane coupling agents, and (meth)acryloyl-containing silane coupling agents. Preferred coupling agents include (meth)acryloyl-containing silane coupling agents.

[0149] Examples of the (meth)acryloyl group-containing silane coupling agent include 2-methacryloyloxyethyltrimethoxysilane, 2-methacryloyloxyethyltriethoxysilane, 2-acryloyloxyethyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropyltriethoxysilane, and 3-acryloyloxypropyltrimethoxysilane. Preferred examples of the (meth)acryloyl group-containing silane coupling agent include 3-methacryloyloxypropyltriethoxysilane.

[0150] The content ratio of the coupling agent relative to the photocurable composition is, for example, 0.1 mass % or more, preferably 0.5 mass % or more, and, for example, 5 mass % or less, preferably 2 mass % or less.

[0151] In addition, additives may be added during the above mixing. That is, the photocurable composition contains additives. Examples of additives include curing accelerators, defoamers, leveling agents, and polymerization inhibitors.

[0152] The content ratio of the additives relative to the photocurable composition is, for example, 10 mass % or less, or preferably 5 mass % or less.

[0153] Thus, a photocurable composition was produced.

[0154] The viscosity of the photocurable composition at 25° C. is 200,000 mPa·s or more, preferably 250,000 mPa·s or more, more preferably 300,000 mPa·s or more, and is 400,000 mPa·s or less.

[0155] When the viscosity is not less than the above lower limit and not more than the above upper limit, the discharge property from the nozzle improves.

[0156] In addition, the measuring method of the said viscosity is demonstrated in detail in the Example mentioned later.

[0157] <Effects>

[0158] The photocurable composition contains an inorganic filler, so that the adhesiveness can be improved, the viscosity can be adjusted, and the ejection property from the nozzle can be improved.

[0159] In addition, the curable resin component includes a multifunctional curable compound. In addition, the multifunctional curable compound includes a first multifunctional curable compound and a second multifunctional curable compound that are different from each other. In addition, the content ratio of the multifunctional curable compound is a predetermined range. Therefore, the adhesiveness and the ejection property from the nozzle are excellent.

[0160] Moreover, the viscosity of the photocurable composition at 25° C. is within a predetermined range. Therefore, the discharge property from the nozzle is excellent.

[0161] In addition, the photocurable composition can be photocured. Therefore, even if the heat resistance of the substrate (described later) to which the photocurable composition is applied is low, the photocurable composition can be cured. In addition, the photocurable composition is excellent in productivity because it can be photocured.

[0162] Furthermore, such a photocurable composition is excellent in adhesiveness and dischargeability from a nozzle and can therefore be suitably used as a sealing material for a liquid crystal display device.

[0163] <Sealing material for liquid crystal display device>

[0164] The sealing material for a liquid crystal display device contains a photocurable composition.

[0165] Since the sealing material for a liquid crystal display device contains a photocurable composition, it is excellent in adhesiveness and dischargeability from a nozzle.

[0166] Specifically, the sealing material for a liquid crystal display device can be suitably used for manufacturing a liquid crystal display device by a liquid crystal dropping method. Hereinafter, a method for manufacturing a liquid crystal display device using the sealing material for a liquid crystal display device will be described in detail.

[0167] Specifically, in the liquid crystal dropping method, as shown in FIG. Figure 1A In this way, the sealing material 2 for liquid crystal display device is applied to the outer periphery of the surface of one electrode-equipped substrate 1 as the first electrode-equipped substrate to form a substantially rectangular sealing pattern 3. At this time, the sealing material 2 for liquid crystal display device is discharged from the nozzle 10.

[0168] As the electrode-bearing substrate 1, for example, a glass substrate, a polymer film (for example, a PET (polyethylene terephthalate) film, a TAC (triacetyl cellulose) film, and a polycarbonate film) can be cited. According to the sealing material for liquid crystal display devices, liquid crystal display devices can be manufactured even with a substrate having low heat resistance, so as the electrode-bearing substrate 1, a polymer film can be preferably cited.

[0169] Then, as referenced Figure 1B In this way, in the uncured state of the sealing material 2 for a liquid crystal display device, droplets 4 of liquid crystal are dropped into the frame of the seal pattern 3 of one substrate with electrode 1 .

[0170] Then, as referenced Figure 1C In this way, another electrode-bearing substrate 5 (the same base material as the electrode-bearing substrate 1) is bonded to the surface of one electrode-bearing substrate as a second electrode-bearing substrate under vacuum, and the sealing material 2 for liquid crystal display device is photocured, thereby manufacturing a liquid crystal display device. Such a liquid crystal display device comprises: a first electrode-bearing substrate 1; a second electrode-bearing substrate 5 arranged opposite to the first electrode-bearing substrate 1; a liquid crystal interposed between the first electrode-bearing substrate 1 and the second electrode-bearing substrate 5; and a cured product of the sealing material for liquid crystal display device, which bonds the peripheral ends of the first electrode-bearing substrate 1 and the second electrode-bearing substrate 5.

[0171] Since the sealing material 2 for a liquid crystal display device has excellent discharge properties from a nozzle, even when the sealing material 2 for a liquid crystal display device is discharged from the nozzle 10 , the coating properties are excellent.

[0172] In addition, since the sealing material 2 for liquid crystal display devices is photocurable, the sealing material 2 for liquid crystal display devices can be cured even if the heat resistance of the substrate 1 is low. In addition, since the sealing material 2 for liquid crystal display devices is photocurable, the productivity is excellent.

[0173] Furthermore, since the sealing material 2 for a liquid crystal display device has excellent adhesiveness, it is possible to reliably bond the one electrode-attached substrate 1 and the other electrode-attached substrate 5 .

[0174] Example

[0175] Next, the present invention is described based on examples and comparative examples, but the present invention is not limited to the following examples. It should be noted that "parts" and "%" are mass references unless otherwise specified. In addition, the specific numerical values ​​of the mixing ratio (containing ratio), physical property values, parameters, etc. used in the following description can be replaced by the corresponding upper limit values ​​(defined as "below", "less than") or lower limits (defined as "above", "exceeding") of the mixing ratios (containing ratios), physical property values, parameters, etc. corresponding to them recorded in the above-mentioned "Specific Implementation Methods".

[0176] <Details of ingredients>

[0177] The trade names and abbreviations of the components used in each Production Example, each Example, and each Comparative Example are described in detail below.

[0178] Ebecryl 3708: the above-mentioned compound (8), manufactured by Daicel-Allnex Co., Ltd., viscosity at 60°C: 3500 mPa·s

[0179] FA-512AS: Monofunctional curable compound, dicyclopentenyloxyethyl acrylate, manufactured by Showa Denko Materials Co., Ltd.

[0180] Ebecryl3700: Bisphenol A epoxy acrylate, viscosity 4300mPa·s at 60℃

[0181] OXE-02: Photopolymerization initiator, ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetyl oxime)

[0182] Omnipol-910: Polyethylene glycol 200-bis(β-4(4-(2-dimethylamino-2-benzyl)butyrylphenyl)piperazine), manufactured by IGM

[0183] SO-C1: Silica particles, inorganic filler, made by Admatechs

[0184] DAW-01: Alumina particles, inorganic filler, manufactured by Denka

[0185] F351: Core-shell particles whose core is a polymer of n-butyl acrylate and whose shell is a polymer of methyl methacrylate, trade name "ZEFIAC F351", manufactured by AICA Industries

[0186] KBE-503 (Shin-Etsu Chemical Co., Ltd.), coupling agent, methacryloxypropyltriethoxysilane, Shin-Etsu Chemical Co., Ltd.

[0187] <Production of Multifunctional Curable Compound>

[0188] Production Example 1

[0189] 116 g of 2-hydroxyethyl acrylate, 0.1 g of p-methoxyphenol (polymerization inhibitor) and 100 g of succinic anhydride were added to a flask, and dry air was introduced, and the mixture was reacted for 5 hours while being refluxed and stirred at 90° C. Next, 170 g of bisphenol A diglycidyl ether was added, and the mixture was reacted for 5 hours while being refluxed and stirred at 90° C. The obtained compound was washed 20 times with ultrapure water. Thus, compound (3) was prepared.

[0190] Production Example 2

[0191] 130 g of 2-hydroxypropyl acrylate, 0.1 g of p-methoxyphenol (polymerization inhibitor) and 148 g of phthalic anhydride were added to a flask, and dry air was introduced, and the mixture was reacted for 5 hours while being refluxed and stirred at 90° C. Next, 170 g of bisphenol A diglycidyl ether was added, and the mixture was reacted for 5 hours while being refluxed and stirred at 90° C. in the same manner. The obtained compound was washed 20 times with ultrapure water. Thus, compound (4) was prepared.

[0192] Production Example 3

[0193] 130 g of 2-hydroxypropyl acrylate, 0.1 g of p-methoxyphenol (polymerization inhibitor) and 100 g of succinic anhydride were added to a flask, and dry air was introduced, and the mixture was reacted for 5 hours while being refluxed and stirred at 90° C. Next, 170 g of bisphenol A diglycidyl ether was added, and the mixture was reacted for 5 hours while being refluxed and stirred at 90° C. The obtained compound was washed 20 times with ultrapure water. Thus, compound (5) was prepared.

[0194] Production Example 4

[0195] 116 g of 2-hydroxyethyl acrylate, 0.1 g of p-methoxyphenol (polymerization inhibitor) and 148 g of phthalic anhydride were added to a flask, and dry air was introduced, and the mixture was reacted for 5 hours while being refluxed and stirred at 90°C. Next, 170 g of bisphenol A diglycidyl ether was added, and the mixture was reacted for 5 hours while being refluxed and stirred at 90°C. The obtained compound was washed 20 times with ultrapure water. Thus, compound (6) was prepared.

[0196] Production Example 5

[0197] 130 g of 2-hydroxyethyl methacrylate, 0.1 g of p-methoxyphenol (polymerization inhibitor) and 100 g of succinic anhydride were added to a flask, and dry air was introduced, and the mixture was reacted for 5 hours while being refluxed and stirred at 90°C. Next, 170 g of bisphenol A diglycidyl ether was added, and the mixture was reacted for 5 hours while being refluxed and stirred at 90°C. The obtained compound was washed 20 times with ultrapure water. Thus, compound (7) was prepared.

[0198] Production Example 6

[0199] A multifunctional curable compound was produced according to the synthesis of epoxy acrylate in Example 1 of JP-A-2011-186486.

[0200] <Production of Photopolymerization Initiator>

[0201] Production Example 7

[0202] According to Synthesis Example 14 of International Publication No. 2017 / 002362, a thioxanthone compound was produced.

[0203] Production Example 8

[0204] According to Synthesis Example 6 of International Publication No. 2017 / 002362, an anthraquinone compound was produced.

[0205] <Production of Photocurable Composition>

[0206] Examples 1 to 13 and Comparative Examples 1 to 4

[0207] The components were mixed into a uniform liquid using a three-roll mill according to the formulations described in Tables 1 and 2. In this way, a photocurable composition was prepared.

[0208] <Evaluation>

[0209] [Viscosity]

[0210] The viscosity was measured for the multifunctional curable compound of each manufacturing example and the photocurable composition of each embodiment and each comparative example. Specifically, the viscosity was measured using an E-type viscometer (TVE-35L-shaped viscometer, manufactured by Toki Sangyo Co., Ltd., rotor name: 3°×R9.7) according to the cone-plate viscometer method of JIS K5600-2-3 (2014). The cone-plate rotation speed during the measurement was 2.5 rpm. Regarding the measurement temperature, it was set to 60°C for the multifunctional curable compound and 25°C for the photocurable composition.

[0211] The viscosity of the multifunctional curable compound of Manufacturing Example 1 at 60°C is 7000 mPa·s. The viscosity of the multifunctional curable compound of Manufacturing Example 2 at 60°C is 6000 mPa·s. The viscosity of the multifunctional curable compound of Manufacturing Example 3 at 60°C is 6600 mPa·s. The viscosity of the multifunctional curable compound of Manufacturing Example 4 at 60°C is 7000 mPa·s. The viscosity of the multifunctional curable compound of Manufacturing Example 5 at 60°C is 5400 mPa·s. The viscosities of the photocurable compositions at 25°C are shown in Tables 1 and 2.

[0212] [Dispensability from nozzle]

[0213] After filling 30g of the photocurable composition of each embodiment and each comparative example into a 10cc syringe, degassing was performed. Then, a low pressure loss nozzle (manufactured by AI MECHATEC: SL nozzle) with a nozzle diameter of 0.25mmφ was installed. After 3 minutes of ejection, the photocurable composition attached to the front end of the nozzle was completely wiped off and allowed to stand for 2 minutes. After 2 minutes, it was visually confirmed whether the photocurable composition was accumulated at the front end of the nozzle. The ejection property from the nozzle was evaluated according to the following benchmarks. The results are shown in Tables 1 and 2.

[0214] {Benchmark}

[0215] ○: The photocurable composition hardly appears at the nozzle tip.

[0216] ×: The photocurable composition accumulates or drips at the tip of the nozzle.

[0217] [Adhesion]

[0218] To 100 parts by mass of the photocurable composition of each embodiment and each comparative example, 2 parts by mass of polymer beads (Micropearl SP manufactured by Sekisui Chemical Co., Ltd.) with an average particle size of 5 μm were added, and the photocurable composition was dispersed by a planetary stirring device. Next, in the center of a 25 mm × 45 mm glass substrate (RT-DM88-PIN, manufactured by EHC) on which a transparent electrode ITO was pre-formed, a photocurable composition (dispersed photocurable composition) was applied with a diameter of 1.5 mmφ using a screen printing plate in such a way that the diameter of a circle after bonding with a thickness of 5 μm becomes about 4.2 mm, thereby forming a sealing pattern. Next, another glass substrate was bonded in the atmosphere in a manner perpendicular to the glass substrate on which the sealing pattern was formed. Then, irradiation was performed at 3000 mJ / cm 2 The photocurable composition was cured by light including visible light (light with a wavelength of 370 to 450 nm). Thus, a test piece was produced.

[0219] For the portion 0.5 mm from the central end of the glass short side of the test piece toward the center direction, an indentation tester (Model 210, made by INTESCO) was used to press vertically at a speed of 37.5 mm / min to measure the stress when the sealing material was peeled off. The value of this stress was used as the bonding strength. Adhesion was evaluated according to the following benchmarks. The results are shown in Tables 1 and 2.

[0220] ◎: The stress is 5 N or more. Or the substrate is broken before the sealing material is peeled off.

[0221] ○: The stress is 3N or more and less than 5N.

[0222] ×: The stress is less than 3N.

[0223] [Table 1]

[0224]

[0225] [Table 2]

[0226]

[0227] It should be noted that the above invention is provided as an exemplary embodiment of the present invention, but it is only a simple example and is not to be interpreted as limiting. Modifications of the present invention that are obvious to those skilled in the art are also included in the claims described below.

[0228] Industrial Applicability

[0229] The photocurable composition and the method for producing a sealing material for a liquid crystal display device of the present invention can be suitably used, for example, for producing a liquid crystal display device. The liquid crystal display device of the present invention can be suitably used, for example, for producing an image display element.

[0230] Explanation of symbols

[0231] 1: The first substrate with electrodes

[0232] 5: The second substrate with electrodes.

Claims

1. A photocurable composition comprising: Curable resin component, Photopolymerization initiator, and Inorganic filler materials, The curable resin component includes a polyfunctional curable compound having two or more ethylenically unsaturated double bonds, The multifunctional curable compound includes a first multifunctional curable compound and a second multifunctional curable compound that are different from each other, The content ratio of the polyfunctional curable compound is 85 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of the curable resin component. The viscosity at 25° C. is 200,000 mPa·s or more and 400,000 mPa·s or less.

2. The photocurable composition according to claim 1, wherein either the first multifunctional curable compound or the second multifunctional curable compound is epoxy (meth)acrylate, The epoxy (meth) acrylate is a reaction product of an epoxy compound and a carboxyl-containing vinyl monomer. The carboxyl-containing vinyl monomer is a reaction product of a hydroxyl-containing vinyl monomer and a polyacid. The epoxy (meth)acrylate is a compound represented by the following formula (1): [Chemistry 1] Chemical 1 In the above formula (1), R1 represents a hydrogen atom or a methyl group, R2 represents a structure derived from a hydroxyl group-containing vinyl monomer, and R3 represents a structure derived from a polybasic acid. 3 . The photocurable composition according to claim 1 , wherein the content of the inorganic filler is 10% by mass or more. 4 . The photocurable composition according to claim 1 , wherein the inorganic filler is at least one selected from the group consisting of silica, alumina and talc.

5. The photocurable composition according to claim 1, further comprising a coupling agent.

6. The photocurable composition according to claim 1, further comprising composite particles, The composite particles include a core and a shell covering the core. 7 . The photocurable composition according to claim 1 , wherein the photopolymerization initiator has at least one skeleton selected from the group consisting of an oxime ester skeleton, a thioxanthone skeleton, and an anthraquinone skeleton. 8 . A sealing material for a liquid crystal display device, comprising the photocurable composition according to claim 1 .

9. A liquid crystal display device, comprising: a first substrate with electrodes; a second substrate with electrodes, arranged opposite to the first substrate with electrodes; liquid crystal interposed between the first substrate with electrodes and the second substrate with electrodes; and The cured product of the sealing material for a liquid crystal display device according to claim 8 is bonded to the peripheral end portions of the first substrate with electrodes and the second substrate with electrodes. 10 . The liquid crystal display device according to claim 9 , wherein the first substrate with an electrode and the second substrate with an electrode are formed of a polymer film.